2001
DOI: 10.1053/rapm.2001.25934
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine premedication reduces maternal requirement for intravenous morphine after cesarean delivery without affecting newborn's outcome

Abstract: The present results indicate that oral clonidine reduces the PCA morphine requirement after C-section without compromising the condition of the fetus or newborn. Further study including larger number of patients would be needed before we conclude that oral clonidine for parturients is safe for their newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[1922] Neonatal health was the main concern for us during the study although earlier studies utilizing 15–150 μg of clonidine during parturition have reported hypotension in mother without any effect on the neonatal Apgar scores. [232834] There was no adverse effect in any newborn in our study that could be attributed to intrathecal clonidine as the Apgar scores were normal and comparable in all the neonates and later, during follow-up, we found that feeding was normal in all the infants.…”
Section: Discussionmentioning
confidence: 48%
“…[1922] Neonatal health was the main concern for us during the study although earlier studies utilizing 15–150 μg of clonidine during parturition have reported hypotension in mother without any effect on the neonatal Apgar scores. [232834] There was no adverse effect in any newborn in our study that could be attributed to intrathecal clonidine as the Apgar scores were normal and comparable in all the neonates and later, during follow-up, we found that feeding was normal in all the infants.…”
Section: Discussionmentioning
confidence: 48%